Food, exercise and life style changes among overweight or obese children in urban population - Kumar K., Santosh; Yashoda, H. T.; Kumar N., Mohan; S., Srinivasa (International Journal of Contemporary Pediatrics, 2017)
Background: Obesity is an important public health problem associated with risk of complications in childhood and increased mortality and morbidity in adulthood.Obesity, which was once considered as a symbol of status and wealth in some cultures is now seen as a public health crisis. In India, the available studies suggest that overweight and obesity is 8.5-29.5% and 15-7.4% respectively among school children between 6-18 years from middle and higher socio economic group. Studies have clearly demonstrated that diet and exercise improve glycemic control and some patients with diabetes treated with diet and exercise alone enter a sustained remission state lasting up to 5 years. Methods: Descriptive study was done at tertiary care center, Bangalore involving two urban schools during the period of 1 year between the age group of 10-18 years. The subjects were selected by using purposive sampling procedure keeping in view the operational feasibility. Results: 187 subjects were enrolled for study after informed consent taken. In the study population 88 were overweight and 99 were obese. The mean BMI of overweight was 24.6 ± 1.5 and obese were 28.8 ± 1.9. In the study population questions regarding adequate fiber intake none consumed green leafy or vegetable soup/stew at least once in a week, which is rich in fiber content. Only 12% consumed fresh fruit juices 4-6 times a week and 26% consumed fruits frequently. Fat intake, 50% consumed fried food items at least 2-3 times/month. 59% of them consumed Pizza, soft drinks and tinned foods at least 2-3 times/month. 38% of them consumed butter on bread or potatoes 2-3 times/month. Level of physical activity 52.9% did mild physical activity, 28.8 % did moderate and 18.1% did severe physical activity. Conclusions: Overweight/obese subjects should be educated regarding their dietary habits. Food items containing rich fiber source intake should be increased and fat intake should be reduced. Regular physical activity should be incorporated.